TINGKAT KERUSAKAN TANAH AKIBAT PRODUKSI BIOMASSA PERTANIAN DI KECAMATAN KUALA CENAKU KABUPATEN INDRAGIRI HULU - Saiful Amri; Besri Nasrul; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research aims to study the land degradation as impact agricultural biomass production Sub-district Kuala Cenaku Indragiri Hulu, Riau Province. The research was carried out with methods of soil survey. Based on field observations that guided map and global positioning observation 4 point to the use of agricultural biomass production and 5 points on the production of forest biomass as a control. Based on Government Regulation No. 7/2006, land quality in Kuala Cenaku is not degradation criteria by agricultural biomass production. In General, value of parameters subsidence, pirit, ground water depth, pH, redox, electric conductivity, bulk density and particle density of the agricultural biomass production is higher than the production of biomass forestry. However, the value of the number of microbes, solum thickness, permeability, moisture content and porosity in agricultural biomass production is lower than on the production of biomass forestry. Key words : Biomass Production, Degradation, Kuala Cenaku